PENERAPAN STRATEGI FIRINGLINE UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS VIII MATERI MEMAHAMI TEKS BERITA - Rosa, Evita; Wartiningsih, Agus; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe title of this research is the application of Firingline strategy to increase student interest in class VIII B on the material to understand the text in SMP Islam Tazkiyah news Pontianak. This type of research is the Classroom Action Research (CAR) has been conducted in two cycles. Descriptive and qualitative terms. The research was conducted in SMP Islam Tazkiyah Pontianak, the research subjects are subjects Indonesian teachers and students of class VIII B is 31 students consisting of 22 women and 9 men. classroom action research procedure there are four steps: planning, implementation, observation, and reflection. The data in this study were obtained using a questionnaire. Data collection tools in this study is in the form of tools such as cameras, observation sheets and documentation on the results of the learning process using a strategy of ongoing Firingline. Results obtained from these studies that the planning is already well underway, because teachers use lesson plans in accordance with curriculum guidelines.Keywords: Strategy Firingline, Interest in Learning,